Integrating Yoga and Counselling: A Phenomenological Exploration of the Client Experience - Beveridge, Samantha N.; Buchanan, Marla J. (Canadian Journal of Counselling and Psychotherapy, 2019)
Yoga is a widely utilized practice with extensive research demonstrating its benefits. Dually certified counsellors are increasingly integrating yoga into their practice. Given the paucity of research examining this integrative therapy approach, a phenomenological investigation was designed to explore and describe the lived experiences of clients engaged in this therapeutic approach. 6 clients described their experience of counselling that integrated yoga through in-depth qualitative interviews. 5 main themes emerged: (a) yoga components; (b) counselling components; (c) structure of the integration of yoga and counselling components; (d) counsellor’s way of being matters; and (e) inclusion of yoga in counselling facilitates processes, including bottom-up processing, affect regulation, affect tolerance, and a whole-person approach. The findings are examined considering the extant literature on the integration of yoga and counselling. Recommendations for the inclusion of yoga in counselling practice and implications for future research are discussed.